THE ROLE OF GOVERNMENT IN PREVENTING THE SPREAD OF HOAX RELATED THE 2019 ELECTIONS IN SOCIAL MEDIA - Mhd. Rasidin; Doli Witro; Betria Zarpina Yanti; Rahma Fitria Purwaningsih; Wiji Nurasih (Pusat Penelitian dan Pengembangan Aplikasi Informatika, Informasi dan Komunikasi Publik (APTIKA dan IKP) Badan Penelitian dan Pengembangan SDM Kementerian Komunikasi dan Informatika, 2020)
The freedom of use of social media has been exploited by a number of people to distribute information that is questionable. The fake news or hoax is disseminated to lead public opinion related certain thing that is motivated by personal and group interests. In 2019, Masyarakat Telematika (Mastel) launched a survey result which stated that 34.60% of Indonesians had received hoax news every day through social media. Starting from this, the government’s role is needed to participate in filtering information circulating on social media. Through this study, the author wants to examine the role of government in preventing and assisting the society in filtering and clarifying hoax news on social media about elections in the political year. This study uses a qualitative approach that is library research. Reference materials are obtained from books, journals, research reports, magazines related to hoaxes, elections, and social media. After the data is collected, the author analyze the data using analysis techniques including data reduction, data presentation, and drawing conclusions. The results showed that the purpose of spreading hoaxes was to earn money and spread the ideology. The rapid development of hoaxes on social media is an urgency for the government to conduct various ways immediately to overcome this, both by increasing the capacity and security within the government and by collaborating with several expert agencies.